Nanotechnology-driven adsorption for the removal of pesticide contaminants from water - A review - Jan, Ulfat; Bhartiya, Shivani; Fatima, Nusrat (Journal of Scientific Agriculture, 2025)
Pesticides are natural or synthetic compounds that are used to protect crops against pests. Pesticides are important as they help to grow more food and increase agricultural productivity by protecting crops from pests, diseases, and weeds. Pesticides have some harmful effects on the environment as they cause soil deterioration, water pollution, harm to non-target organisms, biomagnification, resistance development and disrupt ecosystem services. Pesticides also leave residues in the environment, food, soil and water sources. There are a number of methods for this pesticide elimination from the water. However, the development of a new scientific area, nanotechnology, has become widely used for environmental remediation in recent years. Nanotechnology offers promising solutions for removing pesticide contaminants from water through adsorption techniques. Nano-scale materials have a high specific surface area, changed quantum properties and their small size allows them to reach the target contaminant where micro materials cannot enter. The focus of this review is to study several nano-technology approaches like carbon-nanotubes, grapheme-based nanomaterials, dendrimer nano-adsorbent and nano-crystalline metal oxides for pesticide removal from water by the adsorption process.